Study on Preventive Maintenance Strategy for Road Pavement - Anuar, Abdul Hakim (IRC, 2015)
The increase in road traffic yearly have accelerated the deterioration of road pavement which resulted in the need for more frequent maintenance. This translates into higher maintenance costs and to address this problem, maintenance agencies have to come out with a more economical solution to reduce rate of pavement deterioration through timely preventive maintenance, the use of more durable construction materials, implementation of the right corrective maintenance according to the type of road damage and lastly the design of the pavement itself. This study will be focusing on the maintenance type used by the highway industries in Malaysia. Since Klang Valley is home to networks of interconnected highways operated by various operators, it is chosen to ease the process of this study since it is near to each other. This study will also analyze the strategies used by SILK highway which is the second objective of this study, in term of type of maintenance used and how the management system is applied. For the first objective, series of interview and questionnaire is conducted at four different highway operations office in order to identify their specific opinion on the best type of maintenance system. Based on the results obtained, all four agrees that preventive maintenance is a more cost effective maintenance compared to the costlier corrective maintenance. For the second objective, based on the study conducted at SILK highway. The strategies used for corrective maintenance is to conduct a survey that analyze the state of the pavement condition and highway assets. Then IKRAM will be appointed to conduct Pavement Condition Assessment and based on the data SILK will determine where is the segment that needs addressing. PROPEL which is the contractor will then execute the maintenance works under the highway maintenance team supervision.